3D-printed machines that manipulate microscopic objects using capillary forces - Zeng, Cheng; Faaborg, Maya Winters; Sherif, Ahmed; Falk, Martin J.; Hajian, Rozhin; Xiao, Ming; Hartig, Kara; Bar-Sinai, Yohai; Brenner, Michael P.; Manoharan, Vinothan N. (Nature (London), 2022)
Objects that deform a liquid interface are subject to capillary forces, which can be harnessed to assemble the objects 1 – 4 . Once assembled, such structures are generally static. Here we dynamically modulate these forces to move objects in programmable two-dimensional patterns. We 3D-print devices containing channels that trap floating objects using repulsive capillary forces 5 , 6 , then move these devices vertically in a water bath. Because the channel cross-sections vary with height, the trapped objects can be steered in two dimensions. The device and interface therefore constitute a simple machine that converts vertical to lateral motion. We design machines that translate, rotate and separate multiple floating objects and that do work on submerged objects through cyclic vertical motion. We combine these elementary machines to make centimetre-scale compound machines that braid micrometre-scale filaments into prescribed topologies, including non-repeating braids. Capillary machines are distinct from mechanical, optical or fluidic micromanipulators in that a meniscus links the object to the machine. Therefore, the channel shapes need only be controlled on the scale of the capillary length (a few millimetres), even when the objects are microscopic. Consequently, such machines can be built quickly and inexpensively. This approach could be used to manipulate micrometre-scale particles or to braid microwires for high-frequency electronics. By harnessing capillary forces, 3D-printed machines with cross-sections that vary by height can move floating objects programmatically in two dimensions and even braid filaments without physical contact.